Exploring the associations between substance use and online risk-taking among college students. (4th March 2019) - Gliske, Kate; Dworkin, Jodi; Keyzers, Angela; Jang, Juyoung
ABSTRACT: Background: The rise of the Internet has provided another context in which college students can engage in normative risk-taking behavior. However, little is known about online risk-taking or the extent to which it is associated with substance use. Methods: Heterogeneity in self-reported online risk-taking was explored among 246 U.S. college students (17–23 year old; 60% male; 65% White) using a finite number of discrete online risk-taking profiles. The relationship between different profiles of online risk-taking and substance use was then assessed using multinomial logistic regression. Results: Three unique classes of online risk-taking emerged. Individuals in the high online risk-taking class had significantly higher odds of engaging in lifetime alcohol use, lifetime marijuana use, and lifetime illegal drug use compared to individuals in the low risk-taking class. Substance use was not associated with the probability of membership in the sexual online risk-taking class relative to the low risk-taking class. Conclusions: Results suggest a need for a more nuanced understanding of which students are engaging in online risks and how online risk-taking is associated with substance use.